Is the efficacy of remdesivir so different from that of lopinavir–ritonavir in severe COVID-19? The answer by real time-PCR: a narrative review - Isidoro Duarte, Tiago; Vieira, Cesar; Pimentel, Carlos; Cascão, Mariana; Torre, Marta; Santos-Lima, Joaquim; Sequeira, Tânia; Germano, Nuno; Corte-Real, Rita; Bento, Luís (Anestezjologia Intensywna Terapia, 2021)
This letter discusses the efficacy of current antiviral therapy used in severe COVID-19 infection. Since the first severe cases were documented, several antiviral options have been studied as adjuncts to standard supportive care [1, 2]. Firstly, the combination of lopinavir–ritonavir resurrected from SARS and MERS outbreaks and soon abandoned after the publication of several trials like the randomized controlled trial RECOVERY, which concluded that it was not associated with reductions in 28-day mortality, duration of hospital stay, or risk of progression to invasive mechanical ventilation or death [3]. Remdesivir is currently the only antiviral agent approved for the treatment of COVID-19. It is recommended for use in hospitalized patients who require supplemental oxygen. However, it is not routinely recommended for patients who require mechanical ventilation due to the lack of data showing any benefit at this advanced stage of the disease [4–6].